Reimagining STEM Education in Indigenous Languages: Are Secondary School Physics Teachers Ready? (Federal University Gusau Faculty of Education Journal, 2026)
Persistent underachievement in senior secondary school physics continues to threaten the realization of Nigeria’s STEM development goals. National examination reports from WAEC, NECO, and UTME consistently indicate unsatisfactory performance in Physics, with failure rates exceeding 50% in several years, despite repeated curriculum reforms and pedagogical innovations. This study critically examines language of instruction as a fundamental but underemphasized factor influencing students’ conceptual understanding of Physics, drawing on the renewed advocacy by the Science Teachers Association of Nigeria (STAN) for the integration of indigenous languages into STEM education. Guided by sociocultural and cognitive learning theories, the study synthesizes empirical evidence demonstrating that instruction in learners’ familiar languages reduces cognitive load, enhances comprehension of abstract scientific concepts, and improves long-term retention. Historical insights from the Ife Six-Year Primary Science Project further highlight the pedagogical viability of mother-tongue science instruction while exposing systemic challenges related to policy inconsistency and resource development. Survey data collected from 44 secondary school Physics teachers reveal moderate overall readiness to teach Physics using indigenous languages (mean ≈ 2.37 on a 4-point scale), but limited professional preparation, with only 11.4% reporting prior training in indigenous-language STEM instruction. Inferential analyses show no statistically significant differences in readiness based on gender, school type, teaching experience, or qualification, suggesting that constraints are largely structural rather than individual. The study concludes that while indigenous-language-based Physics instruction holds substantial cognitive and educational promise, its effective implementation requires deliberate policy commitment, systematic teacher training, standardized scientific terminology, and sustained instructional support.